2019
DOI: 10.3390/molecules24010207
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of Aluminum against Acid Activation: Impact of Benzothiazole-Substituted Gallium Phthalocyanine

Abstract: This study describes the adsorption behavior of organic inhibitors at the aluminum-HCl solution interface and their corrosion inhibition performance. The organic inhibitors employed are: 4-(benzo [d]thiazol-2ylthio)phthalonitrile (BTThio) and tetrakis[(benzo[d]thiazol-2-yl-thio)phthalo- cyaninato]gallium(III) chloride (ClGaBTThioPc). The corrosion behavior of these inhibitors is investigated using electrochemical and computational techniques. Open circuit potential results reveal predominant cathodic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 79 publications
0
21
0
1
Order By: Relevance
“…The negative value of indicates the spontaneous adsorption and stability of the adsorbed film onto the steel rebar surface. The calculated by the Langmuir adsorption isotherm indicates that the ammonium phosphate monobasic inhibitor follows the physisorption and chemisorption together [ 54 , 55 , 56 , 57 ] while the Freundlich result suggests the physisorption isotherm [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The negative value of indicates the spontaneous adsorption and stability of the adsorbed film onto the steel rebar surface. The calculated by the Langmuir adsorption isotherm indicates that the ammonium phosphate monobasic inhibitor follows the physisorption and chemisorption together [ 54 , 55 , 56 , 57 ] while the Freundlich result suggests the physisorption isotherm [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon could take place by the reaction between the PIL and the chloride anions, as reported in other works. [ 21,67 ] The cation moiety of the PIL could be electrostatically attracted toward the chloride anions, through the amino functional group, [ 21,68 ] which retarded their arrival toward the surface. On the contrary, the counterion corresponding to the oleate anion could have been chemisorbed on the substrate surface, given that, at the studied pH, aluminum possesses an excess of positive charge.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we have observed that the cp rings peak intensities also became lowered upon adsorption on the aluminium surface. 53 A comparison of the FT-IR spectra of Fcub and Fcuc before and aer adsorption on the aluminium alloy surface are shown in Fig. S10 and S11.…”
Section: Tafel Polarization Measurements the Tafel Plots Or Potentiomentioning
confidence: 99%